2008
DOI: 10.3766/jaaa.19.2.7
|View full text |Cite
|
Sign up to set email alerts
|

Hearing and Balance Screening and Referrals for Medicare Patients: A National Survey of Primary Care Physicians

Abstract: Hearing and balance problems are prevalent among the elderly. Primary care physicians (PCPs) are important pivotal points of entry for ensuring that patients receive needed audiology services. New Medicare beneficiaries are entitled to one-time preventative examinations including hearing/balance screenings. A 35-item questionnaire was developed to assess physicians' participation in, knowledge about, and attitudes toward hearing/balance screenings and referrals for the elderly. The survey was mailed to 710 PCP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
72
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(73 citation statements)
references
References 37 publications
1
72
0
Order By: Relevance
“…161,162,165,167,179,181,188,207,216,242,250,270,271,277 Of these, three studies reported that a GP who had been in practice longer referred less frequently. 162,165,207 Conversely, three studies reported that GPs who had been in practice longer referred more frequently.…”
Section: General Practitioner Factorsmentioning
confidence: 99%
See 4 more Smart Citations
“…161,162,165,167,179,181,188,207,216,242,250,270,271,277 Of these, three studies reported that a GP who had been in practice longer referred less frequently. 162,165,207 Conversely, three studies reported that GPs who had been in practice longer referred more frequently.…”
Section: General Practitioner Factorsmentioning
confidence: 99%
“…242 An additional seven studies reported no association between number of years in practice and referral rate. 161,179,181,227,250,270,271 Overall, three of these studies 162,227,271 were at higher risk of bias and the evidence was graded as conflicting.…”
Section: General Practitioner Factorsmentioning
confidence: 99%
See 3 more Smart Citations